INDONESIA DALAM PEMETAAN EKSPOR KOPI DI ASEAN - Haryoga Tri Herlambang, (2022)
Over the past few years, Indonesia's coffee exports have continued to grow, which is based on an increase in the quantity and value of exports to the ASEAN market. The holding of the Asean Economic Community (AEC) in early 2016 stimulated coffee exporters such as Indonesia to maintain their export quantity, so an analysis of the competitiveness of Indonesian coffee products in the ASEAN market is needed. The government is expected to be able to increase Indonesian coffee exports to the ASEAN market, especially in the era of the ASEAN Economic Community (AEC). Therefore, the purpose of this study is to analyze the competitiveness of Indonesia's coffee export performance to ASEAN countries, especially in competition with Vietnam to increase the coffee market share in ASEAN.